Doha Development Agenda Negotiations on Agriculutal Sector - Siambella, Asiantono (UI Scholars Hub, 2021)
When Doha Round offically opens in Doha, Qatar in November 2001, the parties of the WTO agreed the round named by Doha Development Agenda (DDA). The majority developing countries argues that the previous round was created the regulations whose just make the developed countries gain more profit and dominate global trade. This article gave the information on the DDA development in agriculture, in order to increase the reformation in agriculture to get the fair and equal global trade system, this article gave the proportional picture and position whose shown by the developing countries in the WTO rounds in 3 problems, market access, domestic support, and export subsidies.